Akt-ing Up Just About Everywhere: Compartment-Specific Akt Activation and Function in Receptor Tyrosine Kinase Signaling - Sugiyama, Michael G.; Fairn, Gregory D.; Antonescu, Costin N. (Frontiers in Cell and Developmental Biology, 2019)
The serine/threonine kinase Akt is a master regulator of many diverse cellular functions, including survival, growth, metabolism, migration, and differentiation. Receptor tyrosine kinases are critical regulators of Akt, as a result of activation of phosphatidylinositol-3-kinase (PI3K) signaling leading to Akt activation upon receptor stimulation. The signaling axis formed by receptor tyrosine kinases, PI3K and Akt, as well as the vast range of downstream substrates is thus central to control of cell physiology in many different contexts and tissues. This axis must be tightly regulated, as disruption of PI3K-Akt signaling underlies the pathology of many diseases such as cancer and diabetes. This sophisticated regulation of PI3K-Akt signaling is due in part to the spatial and temporal compartmentalization of Akt activation and function, including in specific nanoscale domains of the plasma membrane as well as in specific intracellular membrane compartments. Here, we review the evidence for localized activation of PI3K-Akt signaling by receptor tyrosine kinases in various specific cellular compartments, as well as that of compartment-specific functions of Akt leading to control of several fundamental cellular processes. This spatial and temporal control of Akt activation and function occurs by a large number of parallel molecular mechanisms that are central to regulation of cell physiology.